Aminophosphonate functionalized carbon material as well as preparation method and application thereof

Through the application of carbon electrode materials functionalized by aminophosphonate in capacitance deionization technology, the traditional thorium separation method has solved the shortcomings in efficiency, economy and selectivity, and achieved efficient and highly selective thorium separation, and supported recycling.

CN119793404AActive Publication Date: 2025-04-11GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311298304.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-11
Estimated Expiration
2043-10-09

AI Technical Summary

Technical Problem

Traditional thorium separation methods such as solvent extractant method and adsorption method have shortcomings in terms of efficiency and economy, and it is difficult to take into account both high adsorption capacity and high selectivity, and there are shortcomings in stability, adsorption equilibrium time, recycling and large-scale preparation.

Method used

An aminophosphonate functionalized carbon electrode material was designed and prepared and applied to capacitive deionization technology for separation of thorium. This material achieves efficient adsorption and selective separation of thorium through an aminophosphonate structure covalently linked to the carbon material matrix.

Benefits of technology

High adsorption capacity and selective separation of thorium are achieved, suitable for efficient enrichment separation of low concentrations of thorium, and the electrode materials loaded with thorium can be used through desorption and regeneration, with good stability and economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793404A_ABST
    Figure CN119793404A_ABST
Patent Text Reader

Abstract

The invention relates to an aminophosphonate functionalized carbon material as well as a preparation method and application thereof. The amino phosphonate functionalized carbon material comprises a carbon material matrix and a structure which is covalently connected with the carbon material matrix and is shown as a formula I. The amino phosphonate functionalized carbon material can be applied to a capacitive deionization technology to selectively adsorb thorium from a mixed solution containing thorium and rare earth, and has high thorium adsorption capacity. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thorium separation, and specifically relates to an aminophosphonate functionalized carbon material and a preparation method and application thereof. Background Art

[0002] High-purity rare earths are widely used in the field of cutting-edge optoelectronic materials. The residual trace radioactive element thorium seriously affects the performance of rare earth functional materials. Therefore, deep separation and removal of the trace radioactive element thorium in rare earths is a prerequisite for the development of high-performance rare earth functional materials.

[0003] Solvent extraction is a classic method for enriching and separating thorium. However, for the separation and removal of trace thorium, it is usually necessary to carry out the process under the condition of a large water-to-oil ratio to improve the enrichment and separation efficiency. However, there are problems such as phase imbalance and loss of extractant caused by organic phase entrainment. Therefore, this method has obvious shortcomings in terms of efficiency and economy. In comparison, the adsorption method effectively solves the problems of phase imbalance, loss of extractant entrainment, and the appearance of three phases.

[0004] CN112387249B discloses a method for adsorbing thorium using a magnetic porous biochar / zinc ferrite composite material. When the initial concentration of thorium is 20 mg / L, the adsorption capacity of the composite material for thorium is 20.81 mg / g.

[0005] CN110449131B discloses an adsorbent and a method for removing radioactive thorium and uranium impurities from high-purity rare earth products. The removal rate of thorium in a high-purity lutetium solution reaches 98.1%.

[0006] CN109651240A discloses an organic ligand H2DTP and a metal organic framework material, their preparation methods and applications, and a method for separating thorium and rare earth. In a mixed solution containing thorium and rare earth, the adsorption capacity for thorium is 360 mg / g, and the separation coefficients of thorium and rare earth are both greater than 6.

[0007] CN105664873A discloses a method for adsorbing thorium using a bridged β-cyclodextrin derivative. The maximum adsorption capacity of this type of adsorbent for thorium ions is 52.2 mg / g, and the maximum adsorption capacity of Mg / g is 52.2 mg / g. 2+ , Pb 2+ 、Zn 2+ , Fe 3+ 、Cd 2+ Interfering ions such as Th 4+ The adsorption capacity was almost unaffected.

[0008] However, it is difficult for traditional adsorption methods to simultaneously achieve both high adsorption capacity and high selectivity for target metal ions. In addition, the shortcomings in stability, adsorption equilibrium time, recyclability, and large-scale preparation have further limited their promotion and application.

[0009] Therefore, it is necessary to develop new and efficient thorium separation methods. Summary of the invention

[0010] In view of the defects of the above-mentioned solvent extraction method and adsorption method, the inventors designed and prepared an aminophosphonate functionalized carbon electrode material, and applied the material to capacitive deionization technology to separate thorium. Experiments have confirmed that the material has a high adsorption capacity for thorium and can be used to selectively adsorb thorium from a mixed solution containing thorium and rare earth, thus completing the present invention.

[0011] In one aspect, the present invention provides an aminophosphonate functionalized carbon material comprising:

[0012] (1) Carbon material matrix;

[0013] (2) A structure shown in formula I covalently linked to a carbon material matrix:

[0014]

[0015] in,

[0016] R1 is selected from C1~C 16 Alkylene;

[0017] R2 is selected from hydrogen, C1~C 16 alkyl;

[0018] R3 and R4 are each independently selected from hydrogen, C1-C8 alkyl, C3-C 10 Cycloalkyl and C6~C 10 Aryl;

[0019] R5 and R6 are each independently selected from C1 to C 16 Alkyl and C6~C 10 Aryl,

[0020] “*” indicates that the carbon material matrix is ​​connected there.

[0021] The carbon material matrix can be selected from any carbon material suitable for use as a conductive substrate, such as artificial graphite, carbon black, linear carbon, activated carbon fiber, carbon / carbon composites, fullerenes, carbon nanotubes, graphene, carbon-coated nanometal particles, more preferably selected from activated carbon fibers, carbon nanotubes, and most preferably carbon nanotubes.

[0022] In some embodiments, R1 is selected from C1 to C 12 Alkylene, such as C1~C 10 Alkylene, C1~C8 alkylene or C1~C6 alkylene.

[0023] In some embodiments, R2 is selected from hydrogen, C1-C8 alkyl.

[0024] In some embodiments, R3 and R4 are the same or different. In some embodiments, R3 and R4 are each independently selected from hydrogen, C1-C6 alkyl, C5-C8 cycloalkyl and C6-C8 aryl.

[0025] In some embodiments, R5 and R6 are the same or different. In some embodiments, R5 and R6 are each independently selected from C2 to C 14 Alkyl and C6-C8 aryl, more preferably C3-C 12 Alkyl and C6~C8 aryl.

[0026] In some embodiments, the formula I can be one or more selected from the following structures:

[0027]

[0028]

[0029] Based on the above structure disclosed in this article, the aminophosphonate functionalized carbon material of the present invention can be synthesized in combination with known or similar methods in the prior art (such as J. Hazard. Mater, 2009, 176 (1): 119-124; CN201410765062.1; CN201611012369.X), or synthesized by a method similar to the method disclosed in the embodiments.

[0030] In some embodiments, the aminophosphonate functionalized carbon material can be prepared by the following method, which comprises the following steps:

[0031] (1) activating the carbon material matrix with a nitric acid solution to obtain a hydroxylated carbon material;

[0032] (2) reacting the hydroxylated carbon material with a halogenated organic amine X-R1-NH-R2 to obtain an organic amine *-O-R1-NH-R2 grafted carbon material, and then reacting the phosphite PH(=O)(R5O)(R6O) and a carbonyl compound C(=O)R3R4 with an amine methylation reaction to obtain an aminophosphonate functionalized carbon material; or

[0033] Hydroxylated carbon materials and halogenated aminophosphonates The aminophosphonate functionalized carbon material is obtained by substitution reaction.

[0034] Wherein, X represents chlorine, bromine or iodine, and R1, R2, R3, R4, R5, R6 and * have the same meanings as described above.

[0035] In order to show the above reaction more clearly, the carbon material was The hydroxylated carbon material is represented by the following formula II, the halogenated organic amine is represented by the following formula III, the organic amine grafted carbon material is represented by the following formula IV, the phosphite is represented by the following formula V, the carbonyl compound is represented by the following formula VI, the aminophosphonate functionalized carbon material is represented by the following formula I-1, and the halogenated aminophosphonate is represented by the following formula VII. The reaction of the above step (2) can be represented by the following reaction formula 1 or 2, but the present invention is not limited thereto. In particular, the hydroxyl group on the carbon material can be one or more:

[0036]

[0037]

[0038]

[0039] In addition, the method may further include a step of pre-treating the carbon material matrix before step (1), for example, the carbon material matrix may be heated in an inert atmosphere and then soaked in a hydrochloric acid solution to remove impurities in the carbon material carrier, but the present invention is not limited thereto. In some embodiments, the inert atmosphere includes but is not limited to nitrogen, argon and other gases that do not react with the carbon material; the heating temperature may be 200-500°C, and the heating time may be 2-24 hours; the concentration of the hydrochloric acid solution may be 1-20% by volume; and the soaking time may be 4-36 hours, but the present invention is not limited thereto.

[0040] In some embodiments, in step (1), the concentration of the nitric acid solution may be 1.0-12 mol / L; the heating temperature may be 80-120° C., and the reaction time may be 2-24 hours, but the present invention is not limited thereto.

[0041] In some embodiments, the substitution reaction of step (2) is carried out in an organic solvent, including but not limited to methanol, ethanol, acetonitrile, tetrahydrofuran, dioxane, the reaction temperature is 25-120° C., and the reaction time is 12-36 hours, but the present invention is not limited thereto.

[0042] In addition, the halogenated aminophosphonate in step (2) can be obtained by subjecting compound III, compound V and compound VI to an amine methylation reaction, as shown in Reaction Scheme 3, but the present invention is not limited thereto:

[0043]

[0044] Wherein, X, R1, R2, R3, R4, R5 and R6 have the same meanings as described above.

[0045] In some embodiments, the above-mentioned amine methylation reaction can be carried out with or without a catalyst and with or without a solvent. The solvent can be, for example, benzene, toluene, xylene, tetrahydrofuran, dichloromethane, chloroform. The catalyst can be, for example, hydrochloric acid, p-toluenesulfonic acid, InCl3, SnCl2, SnCl4, ZnCl2, MgBr2, BF3·Et2O and other Lewis acids. The reaction time is 25 min to 72 h, and the reaction temperature is room temperature to 150°C, but the present invention is not limited thereto.

[0046] The terms C1 to C2 used in the present invention are 16 Alkyl refers to a straight or branched chain alkyl group containing 1 to 16 carbon atoms, such as a straight or branched chain alkyl group having 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16 carbon atoms, including but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, isobutyl, n-pentyl, neopentyl, isopentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, etc. 12 Alkyl, C1~C 10 Alkyl, C1-C8 alkyl, C1-C6 alkyl, C2-C 14 Alkyl and C3~C 12 The meaning of alkyl is similar.

[0047] The terms C1 to C2 used in the present invention are 16 Alkylene refers to the above C1~C 16 The alkyl group loses another hydrogen atom to form a divalent group.

[0048] The terms C3 to C4 used in the present invention 10 Cycloalkyl refers to a saturated cyclic alkyl group containing 3 to 10 carbon atoms including the carbon atoms of the substituent, and the saturated cyclic alkyl group may be a monocyclic or bicyclic group, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, etc., and the substituent may be one or more substituents selected from C1 to C4 alkyl. The meaning of C5 to C8 cycloalkyl, etc. is similar.

[0049] The terms C6 to C 10 Aryl refers to an aromatic group containing 6 to 10 carbon atoms including the carbon number of the substituent, such as phenyl and phenyl substituted with one or more substituents selected from C1 to C4 alkyl, such as tolyl, dimethylphenyl, trimethylphenyl, ethylphenyl, etc. The meaning of C6 to C8 aromatic groups, etc., is similar.

[0050] Experiments have confirmed that the aminophosphonate functionalized carbon material of the present invention can selectively adsorb thorium, and in particular, can selectively adsorb thorium after being prepared into an electrode as an electrode material, thereby separating thorium from rare earth elements.

[0051] Therefore, another aspect of the present invention provides use of the aminophosphonate functionalized carbon material of the present invention in preparing a material or device for adsorbing thorium.

[0052] Another aspect of the present invention provides an electrode plate, which comprises: an electrode substrate, and an electrode material layer on the electrode substrate, wherein the electrode material layer comprises the aminophosphonate functionalized carbon material of the present invention.

[0053] In addition to the aminophosphonate functionalized carbon material of the present invention, the electrode material layer may also include other materials used in the art for preparing the electrode material layer, such as conductive agents, binders, dispersants, etc., but not limited thereto. The conductive agent includes but is not limited to conventional conductive agents such as carbon black, conductive graphite, carbon fibers, etc. and novel conductive agents including carbon nanotubes, graphene and mixed conductive slurries thereof, etc. The binder includes but is not limited to oily binders such as polyvinylidene fluoride (PVDF), aqueous binders such as styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), etc. The dispersant includes but is not limited to anionic wetting dispersants such as carboxylates and sulfates, polymeric superdispersants such as acrylate polymeric dispersants, polyurethane or polyester polymeric dispersants including N-methylpyrrolidone, etc., and cationic wetting dispersants including amine salts, quaternary ammonium salts, pyridinium salts, etc.

[0054] In the electrode material layer, there is no particular limitation on the size of the aminophosphonate functionalized carbon material of the present invention, as long as it is suitable for preparing electrode plates. For example, the mesh size of the aminophosphonate functionalized carbon material after grinding and sieving can be 50-400 meshes, but is not limited thereto.

[0055] In the electrode material layer, there is no particular restriction on the ratio of each component as long as the required performance can be met. For example, the mass ratio of aminophosphonate functionalized carbon material to conductive agent and binder can be 1:0.01-10:0.01-100, but is not limited thereto.

[0056] The electrode plate can be prepared by any suitable method, and therefore, the present invention does not impose any particular limitation on the preparation method. For example, the aminophosphonate functionalized carbon material can be ground and sieved, mixed with a conductive agent, a binder, a dispersant and other optional materials in a certain proportion, stirred to a liquid state, and finally evenly coated on the surface of a titanium plate, and dried to obtain an aminophosphonate functionalized carbon electrode plate.

[0057] There is no particular restriction on the thickness of the electrode material layer, as long as the required adsorption amount is met, therefore, the thickness of the electrode material layer is not particularly restricted in the present invention. The thickness of the electrode material layer can be conveniently controlled by controlling the wet coating thickness, for example, the wet coating thickness can be controlled to be 0.001-0.30 mm, but is not limited thereto.

[0058] Another aspect of the present invention provides a capacitive deionization device, which comprises the electrode plate of the present invention.

[0059] Except for the electrode plate of the present invention, the capacitive deionization device may have any suitable structure of a capacitive deionization device without particular limitation.

[0060] Another aspect of the present invention provides a method for adsorbing thorium, the method comprising the step of passing a thorium-containing feed solution into a capacitive deionization device of the present invention to adsorb thorium from the feed solution. After the thorium is adsorbed, the aminophosphonate functionalized carbon electrode material has thorium adsorbed thereon, and is sometimes referred to as a thoriated electrode material.

[0061] In some embodiments, the method for adsorbing thorium according to the present invention comprises:

[0062] Passing a thorium-containing feed liquid into the capacitive deionization device of the present invention to adsorb thorium from the feed liquid to obtain a thorium-containing electrode material; optionally washing the thorium-containing electrode material with a detergent, and

[0063] The thorium in the electrode material is desorbed by a desorbent.

[0064] The washing process can remove the impurity elements adsorbed by the electrode material and improve the purity of the thorium adsorbed on the electrode material, thereby helping to improve the purity of the final thorium product. The detergent can be nitric acid, sulfuric acid, hydrochloric acid or a mixed solution of the above acids in any proportion. The acidity of the detergent is calculated as the hydrogen ion molar concentration, which is about 0.01 to 1 mol / L.

[0065] The desorption process is used to elute the thorium in the electrode material to obtain a thorium-containing desorption product, and then produce a thorium product. The desorbent is nitric acid, hydrochloric acid, sulfuric acid or a mixed solution of the above acids, and the acidity is about 0.1 to 8 mol / L calculated by the molar concentration of hydrogen ions. In addition, desorbents including EDTA, sodium carbonate, sodium sulfate, etc. can be used.

[0066] The electrode material after desorption can be recycled and used again to adsorb and separate thorium from thorium-containing liquid.

[0067] The thorium-containing liquid contains thorium and mineral acid and other non-thorium elements. The thorium concentration can be about 0.0001-2.0 mol / L, preferably about 0.0003-1 mol / L. In addition, the liquid can also contain other elements such as rare earth, alkali metal, alkaline earth metal, transition metal and non-metallic elements. There is no restriction on the raw materials for preparing the thorium-containing liquid, as long as it contains thorium. In this case, the method of the present invention can selectively adsorb and separate thorium, thereby separating it from non-thorium impurity elements.

[0068] Preferably, the pH of the thorium-containing feed solution can be 0 to 4, preferably 1-4, for example 1.5, 2, 2.5, 3, 3.5, etc., but not limited thereto. Within the above pH range, it is beneficial for the electrode material of the present invention to maintain a relatively high adsorption capacity, thereby efficiently adsorbing thorium. In the case of exceeding the above pH range, the adsorption capacity of the electrode material of the present invention will be reduced, resulting in reduced adsorption efficiency. Therefore, in the case where the pH of the original thorium-containing feed solution is not within the above range, it is preferred to adjust the pH of the original thorium-containing feed solution to within the above range to improve the extraction efficiency of thorium. The thorium-containing feed solution is generally a nitric acid, sulfuric acid or hydrochloric acid solution, but is not limited thereto.

[0069] Unless otherwise specified, the numerical ranges listed in the present invention include the endpoints and all point values ​​therein that are increased or decreased by the smallest unit of the endpoints and all sub-ranges composed of these point values.

[0070] Beneficial Effects

[0071] The carbon electrode material of the present invention has a simple preparation method, a large adsorption capacity for thorium, good selectivity, and is suitable for efficient enrichment and separation of low-concentration thorium. The thorium-loaded electrode material can be desorbed and recycled after power failure and inorganic acid pickling. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 The thermogravimetric curve of the carbon electrode material prepared in Preparation Example 1 of the present invention is shown.

[0073] Figure 2 The XPS high-resolution P 2P spectrum of the carbon electrode material prepared in Preparation Example 1 of the present invention is shown.

[0074] Figure 3 The XPS high-resolution N1s spectrum of the carbon electrode material prepared in Preparation Example 1 of the present invention is shown.

[0075] Figure 4 Schematic showing the capacitive deionization module.

[0076] Figure 5 The SEM image of the carbon electrode surface prepared in Comparative Example 1 is shown. DETAILED DESCRIPTION

[0077] In order to further illustrate the solutions of the present invention, specific embodiments of the present invention are provided to help those skilled in the art understand and implement the present invention, but the present invention is not limited to these embodiments.

[0078] In addition, it should be noted that the structure of the carbon electrode material given in the preparation example of the present invention is schematic and does not constitute a limitation to the present invention.

[0079] Reagents and instruments

[0080] Carbon nanotubes (CNTs) were purchased from Shanghai Titan Technology Co., Ltd. with product number 041045707.

[0081] Porous activated carbon (AC) was purchased from Shanghai Titan Technology Co., Ltd. with product number 013550462.

[0082] Carbon fiber (CF) was purchased from Shanghai Titan Technology Co., Ltd. with product number 041122102.

[0083] Graphene was purchased from Shanghai Titan Technology Co., Ltd. with product number 041122039.

[0084] Graphene oxide (GO) was purchased from Shanghai Titan Technology Co., Ltd. with product number 041402566.

[0085] Fullerene (C 60 ) was purchased from Shanghai Titan Technology Co., Ltd., product number 013220131.

[0086] Activated carbon fiber (ACF) was prepared by gas activation method. First, the carbon fiber (CF) was soaked in ammonium hydrogen phosphate solution for 1 hour, filtered, dried, and then placed in a tubular furnace and heated to 1500°C in a nitrogen atmosphere for carbonization treatment. The heating rate was 8°C / min, and it was heated at 1500°C for 4 hours, then slowly cooled to 850°C at a cooling rate of 5°C / min. When it reached 850°C, air was introduced to oxidize the carbon fiber for 4 hours, and then cooled to room temperature to obtain ACF.

[0087] PVDF was purchased from Shanghai Titan Technology Co., Ltd., product number 013658853, MW 180000.

[0088] Conductive carbon black was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. with product number #101095.

[0089] Organic amines, aldehydes, ketones, dialkyl phosphites and other reagent materials were purchased from Aladdin Reagent Company and were all of analytical grade.

[0090] The liquid was homemade in the laboratory.

[0091] Other reagents (such as acids, organic solvents, etc.) were all commercially available analytical grade reagents.

[0092] The concentration of thorium in the feed solution was determined by ICP-OES (instrument model: PQ9000, manufacturer: Jena) and ICP-MS (instrument model: Agilent 8900, manufacturer: Agilent).

[0093] Preparation Example 1: Preparation of aminophosphonate functionalized carbon nanotubes (1)

[0094]

[0095] (1) Weigh 3.6 g of carbon nanotubes (CNTs) and place them in a crucible. Heat them at 500°C for 4 hours in a muffle furnace under a nitrogen atmosphere, then cool them to room temperature. Transfer the sample to a beaker, soak the heat-treated carbon nanotube sample in 10% hydrochloric acid solution for 24 hours, filter, wash with pure water and ethanol alternately until neutral, and dry to obtain a purified sample.

[0096] (2) The sample in (1) was immersed in 200 mL of 3.2 mol / L nitric acid solution, heated to 100° C. for activation reaction for 6 hours, cooled to room temperature, washed with pure water until neutral, and dried to obtain hydroxylated carbon nanotubes.

[0097] (3) Weigh 2.0 g of hydroxylated carbon nanotubes, 100 mL of tetrahydrofuran, and 1.3 g of 3-chloropropylamine, mix them, and heat them under reflux at 80° C. for 24 hours. After the reaction is completed, cool them to room temperature, filter them, wash them with water until they are neutral, and vacuum dry them to obtain carbon nanotubes grafted with organic amines.

[0098] (4) Weigh 50 mmol of organic amine grafted carbon nanotubes, 50 mmol of di(2-ethylhexyl)phosphite, 52.5 mmol of paraformaldehyde, 100 mg of p-toluenesulfonic acid, and 100 mL of toluene, and heat at 120°C for 12 hours. After the reaction is completed, cool to room temperature, filter, and wash the product alternately with water and ethanol to obtain aminophosphonate functionalized carbon nanotubes. Thermogravimetric analysis, high-resolution P 2P XPS, and high-resolution N1s XPS analysis are performed on the carbon nanotubes. The results are shown in Figure 1-3 .

[0099] 31 P NMRδ P ,ppm:19.39

[0100] Thermogravimetric results ( Figure 1) showed that under nitrogen atmosphere, when heated to 800℃, the mass of carbon nanotubes remained unchanged, while the mass of functionalized carbon nanotubes decreased to a certain extent. After calculation, the grafting rate was about 7.33%, proving that the organic matter was successfully grafted. High-resolution P 2P XPS spectrum of functionalized carbon nanotubes ( Figure 2 ) shows that the peaks at 133.48eV and 134.08eV can be attributed to the phosphorus atoms of the P=O and PO bonds, respectively, where the peak area ratio of PO and P=O is 2:1, which is consistent with the ratio of the number of chemical bonds in the target molecule; the high-resolution N1s XPS spectrum shows that ( Figure 3 ), the binding energy of the amine nitrogen atom appears at 399.58 eV. The above characterization results show that the aminophosphonate is successfully grafted on the surface of carbon nanotubes.

[0101] Preparation Example 2: Preparation of aminophosphonate functionalized porous activated carbon (2)

[0102]

[0103] Except that porous activated carbon (AC) is used instead of carbon nanotubes and diethylphosphite is used instead of di(2-ethylhexyl)phosphite, other steps are exactly the same as those in Preparation Example 1.

[0104] 31 P NMRδ P ,ppm:19.60

[0105] Preparation Example 3: Preparation of aminophosphonate functionalized carbon fiber (3)

[0106]

[0107] Except that acetaldehyde is used instead of polyformaldehyde, N-(3-chloropropyl)hexadecyl-1-amine is used instead of 3-chloropropylamine, di(hexadecyl)phosphite is used instead of di(2-ethylhexyl)phosphite, and carbon fiber (CF) is used instead of carbon nanotubes, the other steps are exactly the same as those in Preparation Example 1.

[0108] 31 P NMRδ P ,ppm:19.45

[0109] Preparation Example 4: Preparation of aminophosphonate functionalized graphene (4)

[0110]

[0111] Except that acetone is used instead of paraformaldehyde, graphene is used instead of carbon nanotubes, and 2-ethylhexylphenyl phosphite is used instead of di(2-ethylhexyl)phosphite, other steps are exactly the same as those in Preparation Example 1.

[0112] 31 P NMRδ P ,ppm:19.59

[0113] Preparation Example 5: Preparation of aminophosphonate functionalized graphene oxide (5)

[0114]

[0115] Except that acetone was used instead of paraformaldehyde and graphene oxide (GO) was used instead of carbon nanotubes, the other steps were exactly the same as those in Preparation Example 1.

[0116] 31 P NMRδ P ,ppm:19.74

[0117] Preparation Example 6: Preparation of aminophosphonate functionalized fullerene (6)

[0118]

[0119] In addition to using fullerene (C 60 ) instead of carbon nanotubes, diphenyl phosphite instead of di(2-ethylhexyl)phosphite, and N-(4-chloro-2-ethylbutyl)ethyl-1-amine instead of 3-chloropropylamine, the other steps are exactly the same as those in Preparation Example 1.

[0120] 31 P NMRδ P ,ppm:19.68

[0121] Preparation Example 7: Preparation of aminophosphonate functionalized carbon nanotubes (7)

[0122]

[0123] Except that diphenylphosphite was used instead of di(2-ethylhexyl)phosphite and N-(4-chloro-2-ethylbutyl)ethyl-1-amine was used instead of 3-chloropropylamine, the other steps were exactly the same as those in Preparation Example 1.

[0124] 31 P NMRδ P ,ppm:19.80

[0125] Preparation Example 8: Preparation of aminophosphonate functionalized activated carbon fiber (8)

[0126]

[0127] Except that heptadecan-9-one is used instead of paraformaldehyde, 4-chloro-2-ethylbutylamine is used instead of 3-chloropropylamine, activated carbon fiber (ACF) is used instead of carbon nanotubes, and diphenyl phosphite is used instead of di(2-ethylhexyl)phosphite, the other steps are exactly the same as those in Preparation Example 1.

[0128] 31 P NMRδ P ,ppm:19.24

[0129] Example

[0130] Prepare a single thorium chloride solution: Take a 0.2 mol / L thorium chloride solution, dilute it to the required concentration with distilled water, and adjust the pH value of the solution with hydrochloric acid and sodium hydroxide.

[0131] Prepare mixed metal ion solution: take single solution of thorium chloride and rare earth chloride respectively, mix them, dilute them with distilled water to the required concentration, and adjust the pH value of the solution with hydrochloric acid and sodium hydroxide.

[0132] Preparation of electrode plates: PVDF was dissolved with dispersant NMP (N-methylpyrrolidone), the mass fraction of PVDF in the solution was 5%, the aminophosphonate functionalized carbon material in Preparation Example 1-8 was used as an electrode material, mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, and evenly coated on the surface of the titanium plate with a wet coating thickness of 0.15 mm, and then vacuum dried.

[0133] The steps of the electrosorption experiment are as follows: the prepared electrode plate is placed in a capacitive deionization (CDI) module, the feed liquid is injected into the CDI device using a peristaltic pump, and the conductivity value of the effluent is monitored by a conductivity meter. After the adsorption is completed, the concentration of the adsorbed metal ions is determined by inductively coupled plasma emission spectroscopy (ICP). Figure 4 A schematic diagram of a capacitive deionization (CDI) module is shown, in which the two outermost acrylic plates are used to fix the CDI module. The solution is input into the device from the lower water inlet and output from the upper water outlet. The second outer layer is composed of two titanium plates coated with electrode materials, namely electrode plates, with a reaction area of ​​50mm*50mm. On the inner side of the two electrode plates are two layers of hollow plastic partitions for separating the two electrodes. A layer of hollow acrylic plate is placed between the two plastic partitions for fixing the plastic partition. The electrical adsorption and separation of metal ions in the solution is carried out in the space formed by the two electrodes.

[0134] Adsorption capacity Q, distribution ratio K d , the separation coefficient β between thorium and rare earth ions Th / RE , cycle performance R is calculated by the following formula.

[0135]

[0136]

[0137]

[0138]

[0139] Where, Q is the adsorption capacity (mg / g), Q1 and Q i are the adsorption capacities (mg / g) of the first electrosorption and the i-th cycle, respectively, C i With C t are the rare earth ion concentrations before and after electrosorption (mg / L), V is the volume of the slurry (L), and m is the mass of the electrode material coated on the surface of the electrode plate (g).

[0140] Examples 1-8

[0141] The following conditions and the carbon electrode materials in Table 1 were used to carry out the electrosorption experiments and calculate the adsorption capacity.

[0142] Thorium chloride solution: thorium ion concentration is 200ppm, initial pH is 3.0;

[0143] Adsorption time: 180 minutes;

[0144] Voltage: U=4.0V.

[0145] The adsorption capacities of different carbon electrode materials are shown in Table 1.

[0146] Comparative Example 1

[0147] Preparation of electrode plate: Prepare according to a preparation method similar to that of activated carbon electrode reported in Nuclear Engineering and Technology, 2021, 53(9), 2926-2936.

[0148] The preparation process is as follows: PVDF is dissolved with dispersant NMP (N-methylpyrrolidone), the mass fraction of PVDF in the solution is 5%, porous activated carbon (AC), PVDF, and conductive carbon black are mixed and stirred in a mass ratio of 8:1:1, and then evenly coated on the surface of the titanium plate with a wet coating thickness of 0.15 mm, and then vacuum dried.

[0149] SEM image of the prepared carbon electrode surface ( Figure 5 ) showed that a large number of holes appeared on the surface of the electrode, and its surface presented an uneven layered structure. This structural feature increased the specific surface area of ​​the material and was beneficial to the adsorption of metal ions.

[0150] Except for the difference in the electrode plates, the electrosorption experiment was carried out and the adsorption capacity was calculated according to the method and conditions of Example 2. The adsorption capacity for thorium ions is shown in Table 1.

[0151] Table 1

[0152]

[0153]

[0154] From the above results, it can be seen that the aminophosphonate functionalized carbon material of the present invention has a high adsorption capacity for thorium. In particular, from the results of Comparative Example 2 and Comparative Example 1, it can be seen that the aminophosphonate functionalized carbon material of the present invention has a significantly higher adsorption capacity for thorium than the unfunctionalized carbon material.

[0155] Experimental Example 9

[0156] The following conditions and the voltages in Table 2 were used to conduct the electrosorption experiment and calculate the separation coefficients of thorium and rare earth ions.

[0157] Mixed solution: The concentrations of Th, La, Gd, and Lu are all 200 ppm, and the initial pH is 3.0;

[0158] Electrode material: Preparation Example 1;

[0159] Adsorption time: 180 minutes.

[0160] The separation coefficients of thorium and rare earth ions under different voltage conditions are shown in Table 2.

[0161] Table 2

[0162] Voltage (V) <![CDATA[β Th / La ]]> <![CDATA[β Th / Gd ]]> <![CDATA[β Th / Lu ]]> 0.3 3.27 1.62 1.29 1.5 3.43 1.69 1.57 2.0 5.96 3.43 2.29 2.5 9.56 4.13 3.67 3.5 12.07 15.31 17.86 4.0 9.77 15.67 7.38

[0163] The results show that this type of electrosorption material has high selectivity for thorium and can be used to separate thorium from rare earths.

[0164] Example 10

[0165] The following conditions and the carbon electrode materials in Table 3 were used to carry out the electrosorption experiments and calculate the adsorption capacity.

[0166] Thorium chloride solution: thorium ion concentration is 200ppm, initial pH is 3.0;

[0167] Adsorption time: 180 minutes;

[0168] Voltage: U=4.0V.

[0169] After the adsorption of the electrode material is completed, hydrochloric acid solution is introduced for desorption and regeneration, and then water is introduced to wash the electrode material to neutrality, and the feed solution is introduced again to measure the adsorption capacity of thorium. This cycle is repeated 5 times.

[0170] The adsorption capacity of different carbon electrode materials under different cycles is shown in Table 3.

[0171] Table 3

[0172]

[0173]

[0174] In summary, the functionalized carbon electrode material prepared by the present invention has the advantages of simple preparation method, large thorium adsorption capacity, good selectivity, stable cycle performance, etc. It can be used to adsorb and remove thorium ions and has good application prospects.

Claims

1. An aminophosphonate functionalized carbon material comprising: (1) Carbon material matrix; (2) A structure shown in formula I covalently linked to a carbon material matrix: in, R1 is selected from C1~C 16 Alkylene; R2 is selected from hydrogen, C1~C 16 alkyl; R3 and R4 are each independently selected from hydrogen, C1-C8 alkyl, C3-C 10 Cycloalkyl and C6~C 10 Aryl; R5 and R6 are each independently selected from C1 to C 16 Alkyl and C6~C 10 Aryl; "*" indicates that it is connected to the carbon material matrix at this location.

2. The aminophosphonate functionalized carbon material according to claim 1, wherein The carbon material matrix is ​​selected from artificial graphite, carbon black, linear carbon, activated carbon fiber, carbon / carbon composite material, fullerene, carbon nanotube, graphene, carbon-coated nano metal particles; and / or R1 is selected from C1~C 12 Alkylene, such as C1~C 10 Alkylene, C1-C8 alkylene or C1-C6 alkylene; and / or R2 is selected from hydrogen, C1-C8 alkyl; and / or R3 and R4 are each independently selected from hydrogen, C1-C6 alkyl, C5-C8 cycloalkyl and C6-C8 aryl; and / or R5 and R6 are each independently selected from C2 to C 14 Alkyl and C6-C8 aryl, more preferably C3-C 12 Alkyl and C6~C8 aryl.

3. The aminophosphonate functionalized carbon material according to claim 1, wherein The formula I is one or more selected from the following structures:

4. A method for preparing the aminophosphonate functionalized carbon material according to any one of claims 1 to 3, comprising the following steps: (1) activating the carbon material matrix with a nitric acid solution to obtain a hydroxylated carbon material; (2) reacting the hydroxylated carbon material with a halogenated organic amine X-R1-NH-R2 to obtain an organic amine *-O-R1-NH-R2 grafted carbon material, and then reacting the phosphite PH(=O)(R5O)(R6O) and a carbonyl compound C(=O)R3R4 with an amine methylation reaction to obtain an aminophosphonate functionalized carbon material; or Hydroxylated carbon materials and halogenated aminophosphonates The aminophosphonate functionalized carbon material is obtained by substitution reaction. Wherein, X represents chlorine, bromine or iodine, and R1, R2, R3, R4, R5, R6 and * have the same meanings as in the cited claims.

5. Use of the aminophosphonate functionalized carbon material according to any one of claims 1 to 3 in the preparation of a material or device for adsorbing thorium.

6. An electrode plate, comprising: An electrode substrate, and an electrode material layer on the electrode substrate, wherein the electrode material layer comprises the aminophosphonate functionalized carbon material according to any one of claims 1 to 3.

7. A capacitive deionization device comprising the electrode plate of claim 6.

8. A method for adsorbing thorium, comprising the step of passing a thorium-containing liquid into the capacitive deionization device of claim 7 to adsorb thorium from the liquid.

9. The method according to claim 8, comprising: Passing the thorium-containing feed liquid into the capacitive deionization device of claim 7 to adsorb thorium from the feed liquid to obtain a thorium-containing electrode material; optionally washing the thoriated electrode material with a detergent, and The thorium in the electrode material is desorbed by a desorbent.

10. The method according to claim 8 or 9, wherein The thorium concentration in the thorium-containing liquid is 0.0001 to 2.0 mol / L, preferably 0.0003 to 1 mol / L; and / or The pH of the thorium-containing liquid is 0 to 4, preferably 1-4; and / or The detergent is nitric acid, sulfuric acid, hydrochloric acid or a mixed solution of the above acids in any proportion; the acidity of the detergent is calculated as hydrogen ion molar concentration and is 0.01 to 1 mol / L; and / or The desorbent is nitric acid, hydrochloric acid, sulfuric acid or a mixed solution of the above acids, and the acidity is 0.1-8 mol / L calculated by hydrogen ion molar concentration.

Citation Information

Patent Citations

  • Purpose and method of amino-contained neutral phosphine extraction agent for extraction and separation of thorium

    CN105734289A

  • Use and method of neutral phosphine extractant used for extracting and separating cerium (IV) or thorium (IV)

    CN107287419A

  • Method for extraction and separation of thorium by use of neutral phosphine extractant

    CN108085491A

Cited By

  • Graded purification and directional recovery process for mixed extraction agent in industrial wastewater

    CN121292569A